The conundrum of clinical trials and standard of care in sub-Saharan Africa – the research nurse perspective. (December 2019) - Frances Ndyetukira, Jane; Kwizera, Richard; Kugonza, Florence; Ahimbisibwe, Cynthia; Namujju, Carol; Sadiq, Alisat; Namudde, Alice; Williams, Darlisha; Abassi, Mahsa; Rhein, Joshua; Boulware, David R; Meya, David B
Background: Nurses form a very important part of the health workforce in sub-Saharan Africa. Research nurses are critical to the implementation of clinical trials. The duties and responsibilities of a research nurse are complex and continue to evolve as new practices and guidelines are formulated. Aims: In this paper, we have highlighted the major contributions of research nurses in HIV clinical trials in sub-Saharan Africa from the unique perspective of Ugandan nurses. Methods: The requirements and challenges of two multi-site, randomised cryptococcal meningitis clinical trials in Uganda were assessed from the perspective of research nurses conducting complex research in resource-limited settings. Results: Over the course of 8 years, approximately 1739 participants were screened and 934 people were enrolled into the two trials. The nurses found that patient education and engagement were among the most important predictors of success in minimising loss to follow-up. Conclusions: Research nurses played a key role in communicating clinical research goals to patients, obtaining informed consent, minimising loss to follow-up, and ensuring that research practices are translated and implemented into standard of care. However, there remains a need to integrate the same level of care provided in clinical research studies to non-study patients.